Conductivity dependent surface plasmon polariton propagation. (19th August 2016) - Ali, Arshad; Bacha, Bakht Amin; Abdul Jabar, M S; Khan, Anwar Ali; Uddin, Rafi; Ahmad, Iftikhar
Abstract: Conductivity-dependent surface plasmon polariton (SPP) propagation is investigated at the interface between a metal and a tripod-type atomic medium. Our theoretical investigations show that the SPP propagation depends on the conductivity of the metallic medium and the coherent driving fields applied in the atomic medium up to a saturation limit. Further, the SPPs drag and rotate with collective spinning of the proposed structure. The rotation is modified with the spin angular velocity of the whole structure. A maximum rotation of ±4 microradians is observed. Our results may find applications in plasmonster technology.